Prednisone raw material characterization and formulation development (Brazilian Journal of Pharmaceutical Sciences, 2017)
Solid dosage forms for oral use, particularly tablets, are the most highly used dosage forms in therapy because they are easily administered, have high productivity and relatively low cost and provide a more stable drug to form a semi-solid net. Numerous parameters influence the quality of the final dosage form. In this study, the dissolution profile of 20-mg prednisone tablets bioequivalent to the reference product and three test formulations were evaluated using stability testing. During the study, prednisone tablets and the active pharmaceutical ingredient (API) prednisone from two different manufacturers were characterized with respect to their physical and physicochemical properties. The results showed that the dissolution profiles of the test batches and the reference product did not retain pharmaceutical equivalence throughout all the stability study. Notably, both samples of API prednisone were of the same crystal form, and any phase transition that occurred during the study could not be attributed to dissolution variation during stability.